Life expectancy in West African countries: Evidence of convergence and catching up with the north - OlaOluwa S. Yaya; Oluwaseun A. Otekunrin; Ahamuefula E. Ogbonna (Statistics in Transition New Series, 2021)
The article aims to investigate the possibility of the convergence and catching up of life expectancy values observed in West African countries with those noted in North African countries. Following the theory of time series convergence, documented in Bernard and Durlauf (1996) and Greasley and Oxley (1997), more robust unit root tests, based on the Fourier nonlinearity and instantaneous breaks proposed in Furuoka (2017), are used in investigating the convergence of each pair of a West African country and its North African counterpart. As no unit root in the differences of the pairs implies convergence, the results obtained by means of the new statistical approach quite outperform those produced by classical unit root tests. The results provide general evidence of the convergence of life expectancy values recorded in West Africa and North Africa.
Keywords: 519; Africa; convergence; Fourier function; life expectancy ratio; nonlinearity; unit root